2016
DOI: 10.1051/0004-6361/201527889
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional direct simulation Monte-Carlo modeling of the coma of comet 67P/Churyumov-Gerasimenko observed by the VIRTIS and ROSINA instruments on board Rosetta

Abstract: Context. Since its rendezvous with comet 67P/Churyumov-Gerasimenko (67P), the Rosetta spacecraft has provided invaluable information contributing to our understanding of the cometary environment. On board, the VIRTIS and ROSINA instruments can both measure gas parameters in the rarefied cometary atmosphere, the so-called coma, and provide complementary results with remote sensing and in situ measurement techniques, respectively. The data from both ROSINA and VIRTIS instruments suggest that the source regions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 35 publications
10
100
0
Order By: Relevance
“…This scenario is in keeping with the observed increase in activities of outgassing and dust ejection with decreasing heliocentric distance (Bockelée-Morvan et al 2015;Della Corte et al 2015;Fougere et al 2016;Fulle et al 2016c). Since the thickness of the dust cover is small relative to the width of a single honeycomb feature, it suffices to quantify the surface erosion in thickness.…”
Section: Thickness Of Surface Erosionsupporting
confidence: 59%
See 3 more Smart Citations
“…This scenario is in keeping with the observed increase in activities of outgassing and dust ejection with decreasing heliocentric distance (Bockelée-Morvan et al 2015;Della Corte et al 2015;Fougere et al 2016;Fulle et al 2016c). Since the thickness of the dust cover is small relative to the width of a single honeycomb feature, it suffices to quantify the surface erosion in thickness.…”
Section: Thickness Of Surface Erosionsupporting
confidence: 59%
“…Kramer & Noack (2016) demonstrated that the pattern of coma brightness conforms to that of dust emission from a homogeneous nucleus, echoing the earlier conclusion by Crifo et al (2002) that the topography per se could already produce complicated near-nucleus dust coma structures, such as collimated jets. Through comprehensive modeling of the gas coma, Fougere et al (2016) found that a homogeneous outgassing model could be improved by taking into account an enhancement from Hapi to better fit the water column densities observed by VIRTIS (the Visible and Infrared Thermal Imaging Spectrometer).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Except for water the most abundant species is CO 2 . Fougere et al (2016) present calculations for the ratio between the CO 2 gas production rate and the H 2 O gas production rate for May 6, 2015, which is in the time interval that shows elevated distances for the cavity. They find that the ratio is 0.04 to 0.05, meaning water is still by far the dominating species.…”
Section: Dynamical Featuresmentioning
confidence: 99%